Cytochromes P450, Oxygen, and Evolution - David F.V. Lewis; Grainné Sheridan (The Scientific World Journal)
The role of the cytochrome P450 superfamily of heme-thiolate enzymes in oxidative metabolism is discussed in the context of evolutionary development. Concordances between the rise in atmospheric oxygen content, elaboration of the P450 phylogenetic tree and the accepted timescale for the emergence of animal phyla are described. The unique ability of the P450 monooxygenase system to activate molecular oxygen via the consecutive input of two reducing equivalents is explored, such that the possibility of oxygen radical generation and its toxic consequences can be explained in mechanistic terms, together with an appreciation of the ways in which this oxygen activating ability has been utilized by evolving biological systems in their adaptation to an increasing atmospheric oxygen concentration over the past two billon years.